ANALISIS RASCH MODEL TES LEARNING OBSTACLE KEMAMPUAN BERPIKIR KREATIF MATEMATIK PADA SISWA SEKOLAH DASAR - Rosita Ainun, - (2020)
This research is motivated by the importance of applying critical thinking skills to students from an early age. The purpose of this study was to determine the analysis of the Learning Obstacle items and to determine the students' ability to do the Learning Obstacle test, the ability to think creatively in elementary school students using the Rasch model. The approach used in the research is qualitative, for the research method the researcher uses descriptive analysis method which in collecting data the researcher uses the documentation collection technique. The data analysis technique uses the rasch model with the winsteps program by using an output table which consists of item fit order, item measure, person measure, person fit. , and summary statistics. The research results found in this study are as follows. The results of the item fit analysis based on the item fit order showed that all the questions had a fit tendency even though there were some questions that did not meet the criteria. But overall, all the questions worked well in what measurement to measure. The level of difficulty of all the questions was categorized into 4 categories, namely difficult, difficult, easy and very easy. After the analysis was carried out, the students' level of ability in working on the questions was divided into 3 groups, namely high, medium, and low. The level of individual suitability (person fit) is used to see the pattern of student responses according to the abilities of each student. The results showed that there were still some students who had inappropriate response patterns, this was due to the low consistency of thinking of these students and even finding the same pattern of students' answers when answering questions. This indicates that there was fraud at the time of processing the questions.